Implementasi Virtual Reality Pada Museum Radya Pustaka - Prasetyo, Purwoko Fajar (2016)
The Museum is one of the tourist objects that provide knowledge about a past incident from objects in the museum. Museum Radya Pustaka is one of the tourist object of the museum located in the city of Surakarta. But many people are still reluctant to visit and gain knowledge of the museum because it is considered less attractive as a tourist destination. to overcome these, need means of information and documentation which is packed with interesting, information about the museum in the form of virtual reality application. This application is created by using software open source Blender. The process of making the application, including the creation of a 3D human object, the museum objects and the museum. then created the animation for the movement runs and also the process of making the system with game logic by setting the Sensor, Controller and Actuator in a Blender so that can be run interactively. The results of the creation of this application is already tested on 4 computers and all the running but only two that can be running normally. That is the hardware with specs of the computer Amd Athlon x 3, 2 GB ram, vga I746 MB and hardware with specs Amd computer processors A10, 8 GB ram, vga 4095 MB. For the hardware specifications of the laptop with the Intel Pentium(r)cpu 2 GB ram vga 2020 779 MB application is running smoothly but for texture display is broken. While the hardware with computer specs intel pentium 4 vga 128 MB 2 GB ram applications run heavy and lag up as well as the look of the texture part not displayed. Conclusions from the test results is this application gives an overview and provide information to users about the content of the museum. This application can provide knowledge especially for who have never visited a museum. The resulting applications require a hefty hardware specifications to run it. many object process rendering is getting longer.